Optimising Human Resource Management as an Effort to Improve Employee Performance through Digital Attendance - Fauzan*, Rizky; Harsono, Kurniawan; Meisandy, Rhaisa Pradila; Barokah, Muhammad; Muhaimin, Muhammad Iqbal (Universitas Syiah Kuala, 2024)
The objective of this study is to uncover enhancements aimed at elevating employee performance standards within Madrasah Aliyah Nurul Falah. The research adopts a qualitative approach. Findings suggest that utilising fingerprint technology for electronic attendance is user-friendly and secure for accurate recording, due to its minimal susceptibility to manipulation. The head of the madrasah conducts a monthly assessment of the computerised attendance system. Any employee found absent without a valid reason will face repercussions as determined by the decisions made. Effective leadership characterised by integrity and consistent implementation of disciplinary measures by madrasa administrators will enhance the efficacy of computerised attendance systems. While the adoption of electronic attendance systems can positively influence employee discipline, occasional violations persist, notably instances of employees arriving late at the madrasah due to diverse reasons.Keywords: Attendance, Performance, Management.